A prototype for IoT based Rice Field Irrigation System - Asnawi, Muhamad Fuat; Syukriasari, Fitri (Politeknik Ganesha Medan, 2019)
irrigation is a very important factor and as a support that will affect agricultural products. The increase in managing agriculture is also very much needed in the era that has entered the current industrial era 4.0. Water becomes a basic resource to support agricultural activities, if there is no water, the activity will not work. In general, Rice field irrigation runs using conventional methods which are carried out from sources such as rivers. The lack of supervision of the irrigation system has made the performance of the irrigation system not optimal. With this, an irrigation canal regulator is needed and along with these problems, a prototype for IoT based Rice Field Irrigation System is made. This prototype has several functions, namely as a regulator of opening and closing irrigation canals by referring to the condition of water level and soil moisture, as well as monitoring the temperature and humidity conditions of the air around the rice fields. This prototype uses a telegram bot as an internet-of-things media control.